2019
DOI: 10.5713/ajas.18.0232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different short-term high ambient temperature on chicken meat quality and ultra–structure

Abstract: Objective This study investigated the effect of different acute heat stress (HS) levels on chicken meat quality and ultra-structure. Methods Chickens were randomly divided into 7 groups to receive different HS treatments: i) 36°C for 1 h, ii) 36°C for 2 h, iii) 38°C for 1 h, iv) 38°C for 2 h, v) 40°C for 1 h, vi) 40°C for 2 h, and vii) un-stressed control group (25°C). Blood cortisol level, breasts initial temperature, color, pH, water holding capacity (WHC), protein so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…However, no difference was observed in pH among different temperature treatments at 4 and 24 h postmortem. A similar pH decline and ultimate pH values after SHE have been reported in previous studies as well [29][30][31]. This indicated that the increase of SHE temperature from 36 °C to 40 °C caused a slower pH decline at early postmortem.…”
Section: Muscle Phsupporting
confidence: 89%
See 3 more Smart Citations
“…However, no difference was observed in pH among different temperature treatments at 4 and 24 h postmortem. A similar pH decline and ultimate pH values after SHE have been reported in previous studies as well [29][30][31]. This indicated that the increase of SHE temperature from 36 °C to 40 °C caused a slower pH decline at early postmortem.…”
Section: Muscle Phsupporting
confidence: 89%
“…In support, previous research indicated that two-hour heat exposure under 40 °C could increase the expression of Hsp70 in chicken breast muscle to more than three times [52], which suggests that SHE of 40 °C might have increased the cellular defensive mechanism in chicken breast meat. Moreover, the chicken PM muscle after antemortem SHE of 40 °C exposure had better meat quality, less mitochondrial damage, greater protein solubility, and higher muscle ber integrity as compared to SHE of 36 °C [30]. Some studies have indicated that Hsp70 can directly interact with PFK1 in chicken PM muscle during the early postmortem period [49] and have a negative correlation with p-AMPK-α[Thr172] [13].…”
Section: Phosphorylation Of Ampkmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, no effect ( p >0.05) of different transportation distances, crating density, and their interactions on 24 h PM meat redness, yellowness, and hue were observed. Zhang et al (2019) also reported an increase in lightness (L*) and decrease in a* and b* of the broiler breasts reared in summer compared to those reared in winter. Bianchi et al .…”
Section: Resultsmentioning
confidence: 90%